Preparation and Discharge Performance of Thin‐Film Thermal Battery. Issue 12 (26th October 2020) - Hu, Jing; Guo, Hao; Li, Cheng-Jie; Zhang, Ying-Chao; Yuan, Jin-Xiu; Zhang, Shan-Shan; Zhao, Li-Li
Abstract : In this study, a thin‐film single cell is successfully prepared by screen‐printing process. The single cell with 100 μm film cathode and 200 μm film electrolyte via screen‐printing technique exhibits a specific capacity of 1163.4 As g −1 up to 1.5 V. For comparison, a single cell with 500 μm pellet cathode and 300 μm pellet electrolyte via powder‐pressing process just presents a specific capacity of 361.3 As g −1 . The enhancement of specific capacity of single cells prepared by the screen‐printing method can be ascribed to the microstructure of the thin film, which improves the diffusion rate of Li + by macroscopically reducing the thickness of the single cell, and thus releases the maximum capacity of the active material. The thin‐film single cell also demonstrates low diffusion impedance, making it potentially suitable for use in a pulse miniaturization thermal battery. This work provides guidance for the potential engineering application of screen‐printing techniques in thermal battery preparation. Abstract : A thin‐film single cell is prepared by a novel screen‐printing method for the first time, exhibiting superior performance in specific capacity and pulsed current discharge. The screen‐printing method can shorten the micro transmission distance of Li +, which makes it possible to be applied in pulse miniaturization thermal batteries and provides guidance for the potential engineering application.